2022
DOI: 10.56093/ijas.v91i12.120806
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aonla (Phyllanthus emblica) genotypes under semi-arid conditions

Abstract: The present study was carried out to evaluate the aonla (Phyllanthus emblica L. syn. Emblica officinalis Gaertner) genotypes for their growth, yield and fruit quality attributes under the semi-arid condition. The evaluated genotypes had significant variability for the observed parameters. Chakaiya and BSR 1 were found comparatively less vigorous amongst selected genotypes. The number of male flowers, female flowers and total number of flowers, on 10 cm length of indeterminate branch varied from 650.67 to 1488.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
(1 reference statement)
4
5
0
Order By: Relevance
“…60 On the other hand, packaging delayed the enzymatic conversion of ascorbic acid to L-dehydro ascorbic acid due to reduced oxygen supply, resulting in vitamin C retention in packed fruits. 61 Comparable results have also been reported by Wu 62 and Nath et al 32 Partial reduction in ascorbic values was also reported by Pal et al 63 during the storage of individually wrapped guava fruits.…”
Section: Discussionsupporting
confidence: 68%
“…60 On the other hand, packaging delayed the enzymatic conversion of ascorbic acid to L-dehydro ascorbic acid due to reduced oxygen supply, resulting in vitamin C retention in packed fruits. 61 Comparable results have also been reported by Wu 62 and Nath et al 32 Partial reduction in ascorbic values was also reported by Pal et al 63 during the storage of individually wrapped guava fruits.…”
Section: Discussionsupporting
confidence: 68%
“…Francis was observed to have the longest leaves, followed by NA-7 and Banarasi, while Anand-2, Anand-1, Chakaiya, Krishna, and NA-10 had the shortest leaves. These variations can be important in determining the suitability of a particular cultivar for different purposes [ 23 ].…”
Section: Species Classificationmentioning
confidence: 99%
“…Fruit weight varied from 25.94 to 33.90 g, with Banarasi having the highest weight (33.90 g), followed by NA-7 (33.76 g), and Kanchan having the lowest weight (25.94 g) [ 21 ]. The fruit length varied from 3.07 to 3.82 cm; Kanchan had the longest fruits (3.82 cm), followed by Krishna (3.70 cm), Banarasi (3.73 cm), and Francis (3.07 cm), who had the shortest fruits, and Aanand-2 (3.12 cm) [ 26 ]. Fruit width between the cultivars ranged from 3.40 to 4.37 cm, with Banarasi having the widest fruit (4.37 cm), followed by Chakaiya and NA-7 (4.00 cm), and with Francis having the narrowest fruit (3.40 cm), Anand 2 having the next-smallest fruit (3.41 cm), and Anand-1 having the smallest fruit (3.40 cm) [ 16 ].…”
Section: Species Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest respiratory activity (81.1 mg CO 2 per kg per h) with minimum loss and 11 days of extended shelf life in CFB under ambient conditions for the NA-7 cultivar of amla was reported. 136 A perforated polythene bag was found to be useful in reducing the physiological loss with acceptable physiochemical quality of amla fruits. The fruits had an extended shelf life of 15 days at ambient temperature after treatment with 6% waxol and 4 × 10 5 μL cycocel chlormequat chloride (CCC)/L.…”
Section: Packaging and Storage Of Amla Fruitsmentioning
confidence: 99%